Epley’s maneuver versus Semont’s maneuver in treatment of posterior canal benign positional paroxysmal vertigo - P. V., Ajayan; P. F., Aleena; Jacob, Anju Mariam (International Journal of Research in Medical Sciences, 2017)
Background: Benign paroxysmal positional vertigo (BPPV) is characterized by brief but violent attacks of paroxysmal vertigo provoked by certain positions of the head. BPPV is the most common cause of vertigo, resulting from migration of otoconia into the semicircular canals. Majority of patients have posterior canal BPPV. Epley’s Canalith Repositioning and Semont Liberatory Maneuver have been shown to be highly efficacious in the successful treatment of posterior canal BPPV. The main objective of this study was to compare the efficacy of Epley’s maneuver versus Semont’s maneuver in the management of benign paroxysmal positional vertigo. Methods: This study was conducted in the Department of Otorhinolaryngology of a rural Medical College in Kerala, for a period of one and half year, from January 2015 to June 2016. It was an observational prospective cohort study. 200 patients with posterior canal BPPV were enrolled in this study based on inclusion and exclusion criteria. Patients were allotted alternatively to Epley’s group and Semont’s group, 100 patients in each group based on the treatment maneuvers they underwent. Efficacy of maneuvers were assessed at the end of 1st week, 1st month and 3rd month on the basis of resolution of symptoms and Dix-Hallpike negativity. Results: Of the 100 cases managed by Epley’s maneuver 95 cases showed complete relief of symptoms after 3 months. Out of 100 cases managed by Semont’s maneuver, 94 cases showed complete recovery after 3 months. The results were compared by Chi square test, as the data was mainly qualitative in nature. The results of both the groups were compared at the end of 1st week, 1st month and 3rd month, which revealed that both the Semont’s and Epley’s maneuver are equally effective in the treatment of posterior canal BPPV. Conclusions: Both Epley’s and Semont’s maneuver are equally effective for treating the patients of posterior canal benign paroxysmal positional vertigo.